Perlindungan Hukum Konsumen Penyandang Disabilitas Dalam Angkutan Umum Bus Antar Kota - Pratiwi Puspitho Andini (Riau Law Journal, 2022)
The ease of accessibility of public transportation buses between cities which is one of the needs in traveling between cities is certainly needed special facilities for consumers with disabilities. In some cases there are still many intercity bus service businesses that rule this out, not infrequently intercity bus businesses still generalize consumers with disabilities with other consumers. Based on this, the author formulated the formulation of the following problems: 1). What is the form of legal protection for consumers with disabilities who experience losses in the form of rights due to the lack of facilities in public transportation buses between cities. 2). What are the legal consequences for Intercity Bus businesses that harm consumers due to the lack of special facilities for people with disabilities. The method of writing in this journal writing uses normative juridical research types, with a statutory approach and a conceptual approach. Legal materials consist of primary legal materials, secondary legal materials, and non-legal materials. Legal materials consist of primary legal materials, secondary legal materials, and non-legal materials. The results of the discussion of this journal can be concluded as follows: Legal protection for consumers with disabilities such as Faisal Rusdi who suffered losses in the form of rights due to the lack of special facilities in public transportation buses between cities in the form of Internal, this protection is packaged by the parties themselves when making an agreement, if anyone violates one of them will be sanctioned, then more appropriately protection that is external because it is very important.  Protection is needed by the government due to the many disabled consumers who experience losses in the form of unmet rights while traveling using Intercity Bus Public Transportation services. The form of responsibility of intercity bus public transportation business actors that has been regulated in Law No. 22 of 2009 concerning Traffic and Road Transportation must be an obligation. In the Act has also been mentioned for public transportation business actors if they do not provide services, especially to consumers with disabilities, and will be subject to administrative sanctions.Keywords : consumer protection, public transport, persons with disabilities.